The Effect of Papain Enzyme Concentration on Protein Hydrolysate of Mackerel fish (Rastrelliger sp.) - Reinhard Nuary M. Ambarita; Edison Edison; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aimed to investigate the effect of different concentrations of papain enzyme and the best concentration to produce protein hydrolysate from mackerel fish. The research methods used were experimental and with non-factorial completely randomized design (CRD). The treatments used were different concentrations of papain enzyme,each 0% (P0), 12% (P1), 14% (P2), 16% (P3). The parameters tested were consisted of chemical composition, analysis of dissolved protein content using the Bradford method, and analysis of Non Protein Nitrogen (NPN). The chemical composition of mackerel produced is was 14.53% water content, 55.44% protein content, 5.02% ash content, and 14.85% fat content. The results of the analysis showed that the use of different concentrations of papain enzymes affected the protein hydrolyzate of mackerel.The papain concentration of 14% (P2) was the best concentration to produce protein hydrolysate of mackerel with a dissolved protein content of 0.7996 mg/ml and a value of Non Protein Nitrogen (NPN) of 7.2659 mg/ml. Keyword: Fish protein hydrolyzate,Mackerel, Papain Enzyme